Assessing the functional asymmetry of the Bacillus subtilis MutL homodimer - Liu, Linda (My University, 2017)
DNA mismatch repair corrects base-base mismatches and small insertion/deletion loops generated during normal DNA replication. If left unrepaired, these errors become permanent mutations and can lead to increased susceptibility to cancer. In most prokaryotes and all eukaryotes, the mismatch repair protein MutL is a sequence-unspecific endonuclease that plays an essential role in the strand discrimination step of this pathway. Prokaryotic MutL forms homodimers with two endonuclease sites, whereas eukaryotic MutL homologs form heterodimers with a single active site. To elucidate the mechanistic differences between prokaryotic and eukaryotic MutL, we tested whether both endonuclease sites are necessary for prokaryotic MutL nicking activity. MutL interaction with the processivity clamp is required to stimulate endonuclease activity. Therefore, we also tested whether both subunits of the MutL dimer needed to interact with the processivity clamp. To this end, we engineered a system to independently manipulate each protomer of the homodimer. We demonstrated that prokaryotic MutL is regulated by the processivity clamp to act in a similar manner to eukaryotic MutL with only one functional site contributing to the endonuclease activity. We also devised a strategy to stabilize the transient interactions between MutL, the β-clamp, and DNA through disulfide bridge crosslinking and heterobifunctional crosslinking. Stabilizing transient protein-protein and protein-DNA interactions will help optimize future structural studies in obtaining the ternary complex for mechanistic insights to the MutL endonuclease activity and regulation imposed by the β-clamp.
Keywords: MutL; mismatch repair; homodimer; DNA; endonuclease activity